Review on "Ecological Implications of Minilivestock" - Boedhihartono Boedhihartono (Journal of Tropical Ethnobiology, 2005)
The book edited by Prof. M.G. Paoletti comprised of 29 articles on minilivestock. It is indeed a quite interesting book opening our mind that different people are exploiting different resources beyond our imaginations The articles describe from all sort of consumed small invertebrates such as termite, honey pot ant, various forms of larvae such as of caddis fly, larvae of Dobson fly, instars caterpillar larvae, and also other insects such as locust, giant water bugs, crickets, 'gastropods, etc., include a number of small vertebrates such as frogs, birds, turtles, reptiles, rats, porcupines and others . This book is also well illustrated with interesting pictures of the subjects. The book begins with an introductory article by M.G. Paoletti and A.L Dreon. It describes a large number of minilivestock which becomes the potential protein resource in some areas. They are largely consumed by people around the world and considered as alternative food resources. Although the kind of minilivestock described in this book is only a part of so many other consumable creature found in this planet, in fact it offers description on the varieties of different small animals either invertebrates or vertebrates which are quite familiar to different ethnic groups dispersed in this world. It is reasonable therefore that both expressed their concern on the possible extinction of species and the loss of traditional knowledge which are most of them not well recorded yet. In one hand there are so many tribal societies which are fast adopting new way of life and becoming alienated to their inherited customs and practices. They do not consume any more what they have traditionally consumes. In the other hand the massive mobilization of capital has destroyed the natural environment leading to the lost of the habitat of so many organisms formerly available as protein resources for the indigenous or tribal people. This book is probably one of the rarest of the kind. The Paoletti and Dreon have rightly summarized their concerns on the inadequate understanding of local knowledge, on the possible extinction of species, and the arguments of why minilivestock is important. The practice of consuming small creature probably has already taken place since the beginning of human long history. A long list of animals can probably still be deduced not only what the authors of the book have presented, but we also could enrich (our knowledge) from the fact that some of the Chinese restaurants still serve various plates of different animals as delicacy: meat of reptiles, monkeys, various sea creatures and even